Cephalalgia against the background of systemic mastocytosis: a clinical case - P. I. Kuznetsova; M. M. Tanashyan; A. L. Melikyan; I. N. Subortseva; A. A. Raskurazhev (Бюллетень сибирской медицины, 2021)
The article presents a clinical case of comorbid pathology – development of migraine against the background of systemic mastocytosis. The classification and clinical manifestations of systemic mastocytosis, a rare blood disease, are given.This clinical case illustrates an example of excessive mast cell degranulation (with the release of proinflammatory and vasodilating agents as a result of mast cell pathology). In this regard, in addition to the pathogen-specific therapy for systemic mastocytosis (including prevention of mast cell degranulation), it seems important to describe the effectiveness and the possibility of prescribing preventive and emergency therapy for migraine against the background of the underlying hematological disease – systemic mastocytosis.Treatment of cephalalgia in patients with mastocytosis is a complex clinical task, in the solution of which it is necessary to take into account serious limitations in prescription of acetylsalicylic acid and other non-steroidal anti-inflammatory drugs.